Collaborative research: Potential and limitations of participative social cartography - Pablo Saravia-Ramos; Débora Vega-Valdés; Luis Espinoza-Almonacid; Paulo Gutiérrez-Soto (Íconos, 2021)
The article discusses the potential and limitations of participative social cartography. This evaluation is derived from insights gathered from the use of this method in research done with two cooperatives in the Valparaiso region in Chile. The first of them is involved in the production of natural wine, and the second in the commercialization of foodstuffs and other non-food products. In these methodological exercises, mapping played a crucial role and during them both researchers and subjects went through four crucial stages: design, goal-setting, implementation and analysis. In order to achieve results, it was necessary to employ a mix of virtual and face-to face encounters, adapting the methodology not only to the needs and internal dynamics of the cooperatives, but also to the conditions imposed by the COVID-19 pandemics. When comparing the different findings it becomes evident that cartographic techniques need to be adapted to the rhythms and peculiarities of each organization. The text arrives at the conclusion that the co-building of knowledge must be grounded on horizontal participation, in dialogue and in the use of interdisciplinary resources. These are key features in collaborative research methodology. The article questions the relationships which are established between researchers and social organizations. At the same time, thanks to its collective, situated, dynamic and creative condition, it enables a fruitful discussion about the ways in which participative social cartography can contribute to the debate about the linkages between research and territory. Only in this way, it seems possible to build a shared understanding of space.